Emergency Contraception: Exploring the Knowledge, Attitude and Practices of Engineering College Girls in Nagpur District of Central India - Relwani, Nisha; Saoji, Ajeet; Kasturwar, N.B.; Nayse, Jaydeep; Junaid, Mohd; Dhatrak, Poonam (National Journal of Community Medicine, 2012)
Background: The major factor limiting the use of EC may be inadequate information about their effectiveness and availability or unfavorable opinions about their safety due to misinformation. So the study was carried to assess the knowledge, attitude and practice of EC among engineering college girls. Methods: A cross-sectional survey was conducted in an engineering college. All girls from a field were included in the study. Data was collected by a predesigned, pre-tested, self-administered multiple response questionnaires. Results: A total of 8(5.7%) reported that they had previously used ECPs. An association was found between users and their level of knowledge. Users had Average/Good knowledge as compared to non–users (OR-12.51). A strong association was found between source of information and level of knowledge. In other words, respondent receiving information from the Health Personnel (OR 21.49) and Audio-Visual Media (OR 10.2) were more likely to have good or average knowledge as compared to family and friends (OR 6). Conclusion: Knowledge of emergency contraception by students is low and the method is still underused. Strategies to promote use of emergency contraception should be focused on spreading accurate information through medical sources, which have been found to be reliable and associated with good knowledge on emergency contraception.